Propagating characteristics of mesospheric gravity waves observed by an OI 557.7 nm airglow all-sky camera at Mt. Bohyun (36.2° N, 128.9° E) - J.-Y. Hwang; Y.-S. Lee; Y. H. Kim; H. Kam; S.-M. Song; Y.-S. Kwak; Y.-S. Kwak; T.-Y. Yang (Annales Geophysicae, 2022)
We analysed all-sky camera images observed at Mt. Bohyun observatory (36.2∘ N, 128.9∘ E) for the period 2017–2019. The image data were acquired with a narrowband filter centred at 557.7 nm for the OI airglow emission at ∼ 96 km altitude. A total of 150 wave events were identified in the images of 144 clear nights. The interquartile ranges of wavelength, phase speed and periods of the identified waves are 20.5–35.5 km, 27.4–45.0 m s−1 and 10.8–13.7 min with the median values of 27.8 km, 36.3 m s−1 and 11.7 min, respectively. The summer and spring bias of propagation directions of north-eastward and northward, respectively, can be interpreted as the effect of filtering by the prevailing winds in the lower atmosphere. In winter the subdominant north-westward waves may be observed due to a nullified filtering effect by slow northward background wind or secondary waves generated in the upper atmosphere. Intrinsic phase speeds and periods of the waves were also derived by using the wind data simultaneously observed by a nearly co-located meteor radar. The nature of vertical propagation was evaluated in each season. The majority of observed waves are found to be freely propagating and thus can be attributed to wave sources in the lower or upper atmosphere.